Incidence and risk factors for macular oedema after primary rhegmatogenous retinal detachment surgery: a prospective single‐centre study. Issue 3 (16th June 2021) - Gebler, Marie; Pfeiffer, Sebastian; Callizo, Josep; Hoerauf, Hans; Feltgen, Nicolas; Bemme, Sebastian
Abstract: Purpose: To assess the incidence of cystoid macular oedema (CME) diagnosed by spectral domain optical coherence tomography (SD‐OCT) after primary rhegmatogenous retinal detachment (RRD) surgery. Methods: From April 2016 to October 2017, 150 eyes of 150 patients presenting with primary RRD were included consecutively in this prospective single‐centre study. Patients with the following characteristics were excluded: previous vitreoretinal surgery, combined cataract surgery, preoperatively presentation with any intraocular or systemic inflammatory condition, visible macular oedema or epiretinal membrane (ERM) on funduscopy. SD‐OCT (Spectralis, Heidelberg Engineering) was conducted 3 and 6 weeks after surgery. Results: One hundred and twenty‐eight of the 150 patients completed the study, of whom 107 (age: 61.7 ± 11.5 years, mean ± SD) showed successful retinal attachment during follow‐up visits. The most frequent operation method was scleral buckling (54.2%), followed by vitrectomy (25.2%) and the combination of both techniques (20.6%). Postoperative SD‐OCT revealed CME, neurosensory detachment and ERM in 18.7, 31.8 and 32.7% of all cases, respectively. The risk of postoperative CME was significantly elevated in patients with ERM (42.9 versus 6.9%, p < 0.001). In addition, patients with initial detachment of the macula had more postoperative CME (26.5 versus 11.1%, p = 0.044). BCVA improvement was significantly lower in patients with CME compared to patients without 6 weeks after surgery for macula‐on RRD. Conclusions: This prospective study confirmed that postoperative CME is a frequent complication after RRD surgery; we identified ERM and macula‐off RRD as potential risk factors. As CME potentially delays visual recovery, postoperative follow‐ups should include SD‐OCT.